Food Security Amongst Small Grains and Long Grains Smallholder Farmers of Masvingo Province in Zimbabwe - Mapfumo, Alexander (Journal of Social Economics Research, 2017)
This study compared the food security status for small grains and long grains smallholder farmers and analysed the factors that affect food security status for smallholder farmers in Zimbabwe. The study was conducted in Masvingo Province of Zimbabwe and the respondents were stratified into small grains cultivators and long grains cultivators. Data used in the analysis of food security was collected through a researcher administered structured questionnaire. The results established that the adoption of small grains is widespread within the province. Demographic and socio-economic characteristics had an effect on the dependence of either small grains or long grains farming. The results of the study revealed that both small grains and long grains smallholder farmers had at least attained primary education which reveals that all farmers are functionally literate. Results of the Household Dietary Diversity Score HDDS revealed that on average 76 percent of small grains smallholder farmers were measured to be food secure whilst only 41 percent of long grains farmers were food secure. The (HDDS) reflected the dietary diversity consumed by members of the household in the previous 24 hours Similar trends were observed from the descriptive statistics which showed that small grains smallholder farmers consumed relatively greater percentage of nutritious food groups than long grains smallholder farmers. Results of the Binary logit regression model indicated that the significant factors which explain food security status for smallholder sampled households are farming activity, education, number of livestock, remittances, income and access to credit.